DETEKSI DINI OBESITAS ANAK PASCA PANDEMI COVID-19 DAN EDUKASI DI SEKOLAH DASAR NEGERI 022IV JAMBI - Harahap, Huntari; Tarawifa, Susan; Aurora, Wahyu Indah Dewi; Kusdiyah, Erny; Maria, Ima (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
ABSTRACTThe COVID-19 pandemic has brought about significant alterations in human activities, affecting individuals across all walks of life, including school-age children. These changes in activity patterns have had implications for health, particularly in the realm of obesity. Childhood obesity can lead to an increased incidence of chronic diseases in the future, such as hypertension and diabetes mellitus. Community engagement efforts have been undertaken with the aim of early detection of obesity through nutritional screening and educational interventions. This initiative was carried out at Public Elementary School 022/IV Jambi, with a participant cohort of 50 individuals representing students from grades 2 to 5. Anthropometric measurements were conducted on all students, followed by the provision of educational sessions. The nutritional screening results revealed 32% of children classified as normal, while 68% were identified as malnourished, and 30% were classified as obese. Regular monitoring and evaluation by relevant stakeholders are imperative to mitigate the incidence of malnutrition, particularly obesity, in children.Keywords: pandemic, obesity, nutrition, students ABSTRAKSelama masa pandemi covid-19 terjadi perubahan yang signifikan terhadap aktivitas manusia (sedentary life) tanpa terkecuali, salah satunya adalah siswa sekolah. Perubahan aktivitas ini berdampak pada kesehatan, yakni obesitas. Obesitas pada anak dapat meningkatkan kejadian penyakit kronis di masa mendatang, seperti hipertensi dan diabetes mellitus. Pengabdian masyarakat yang dilakukan bertujuan untuk deteksi dini obesitas melalui skirining gizi serta pemberian edukasi. Kegiatan ini dilakukan di Sekolah Dasar Negeri 022/IV Jambi dengan jumlah peserta 50 orang yang mewakili siswa kelas 2-5. Pengukuran antropometri dilakukan pada seluruh siswa, kemudian siswa diberikan edukasi. Hasil skrining gizi didapatkan 32% anak normal, dengan 68% anak malnutrisi, 30% anak obesitas. Diperlukan pemantauan dan evaluasi berkala dari pihak-pihak terkait untuk menurunkan kejadian malnutri, khususnya obesitas pada anak.Kata kunci: pandemi, obesitas, gizi, siswa